2016
DOI: 10.1128/jb.00664-15
|View full text |Cite
|
Sign up to set email alerts
|

Association of O-Antigen Serotype with the Magnitude of Initial Systemic Cytokine Responses and Persistence in the Urinary Tract

Abstract: Urinary tract infection (UTI) is one of the most common ailments requiring both short-term and prophylactic antibiotic therapies. Progression of infection from the bladder to the kidney is associated with more severe clinical symptoms (e.g., fever and vomiting) as well as with dangerous disease sequelae (e.g., renal scaring and sepsis). Host-pathogen interactions that promote bacterial ascent to the kidney are not completely understood. Prior studies indicate that the magnitude of proinflammatory cytokine elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…S3 in the supplemental material and C57BL/6 mice from the experiment shown in Fig. S4 were (Continued on next page) (44). Additional factors produced during UTI that recruit and activate neutrophils and regulate antibacterial defenses include CCL2 (MCP-1), CCL5 (RANTES), TNF-␣, and IFN-␥ (22,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S3 in the supplemental material and C57BL/6 mice from the experiment shown in Fig. S4 were (Continued on next page) (44). Additional factors produced during UTI that recruit and activate neutrophils and regulate antibacterial defenses include CCL2 (MCP-1), CCL5 (RANTES), TNF-␣, and IFN-␥ (22,(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our predictive model for disease severity predominately relates to cytokines and chemokines involved in neutrophil and monocyte recruitment to the site of infection. Prior studies in young mice have shown that inoculation with E. coli induces TNF-␣, IL-1␤, IL-6, IL-10, IL-17, KC (CXCL1), RANTES (CCL5), LIX (CXCL5), and IFN-␥ during the course of infection (28,(44)(45)(46), and inoculation with P. mirabilis induces CCL2 (MCP-1), RANTES, KC, IL-6, IL-10, IL-17A, IL-1␤, TNF-␣, and IFN-␥ (33). Our cytokine and chemokine data are in agreement with these studies and uncovered differences in urine levels of IL-1␤, IFN-␤, CCL5 (RANTES), CXCL5 (LIX), and CCL2 (MCP-1) upon direct comparison of E. coli UTI to P. mirabilis UTI across the entire cohort of mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS from E. coli O111:B4 has been used in numerous studies for surrogate of infectious pathogenesis in the murine host (e.g., systemic inflammatory response syndrome or sepsis). It is recognized that LPS O‐antigen loci from different uropathogenic E. coli strains impact the immune response of the host . Whether a different type of LPS might induce a different GM‐CSF response (e.g., a persistent response, no response, higher intensity response, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that LPS O-antigen loci from different uropathogenic E. coli strains impact the immune response of the host. 26 Whether a different type of LPS might induce a different GM-CSF response (e.g., a persistent response, no response, higher intensity response, etc.) in urothelial cells is unknown.…”
Section: Discussionmentioning
confidence: 99%